2018
DOI: 10.3389/fimmu.2018.00256
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-6 Inhibits IL-27- and IL-30-Mediated Inflammatory Responses in Human Monocytes

Abstract: Interleukin (IL)-30, the IL-27p28 subunit of the heterodimeric cytokine IL-27, acts as an antagonist of IL-27 and IL-6 signaling in murine cells via glycoprotein 130 (gp130) receptor and additional binding partners. Thus far, functions of IL-30 have not been fully elucidated in human cells. We demonstrate that like IL-27, IL-30 upregulated TLR4 expression to enhance lipopolysaccharide-induced TNF-α production in human monocytes; however, these IL-30-mediated activities did not reach the same levels of cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 44 publications
(75 reference statements)
1
39
0
2
Order By: Relevance
“…We also demonstrated that all egc operon nonclassical SAgs have specific interaction with gp130, showing a similar kinetic behavior (Figure 10). The physiological role of these interactions could be explained considering that SAgs block gp130, preventing IL-6 stimuli and the activation of STAT-3 pathway, which is needed for the expression of IL-30 in monocytes (73). Since it has been suggested that IL-30 could be involved in the sepsis-control-modulating cytokines secreted by NKT cells (83), inhibition of the synthesis of IL-30 would suit the spread of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that all egc operon nonclassical SAgs have specific interaction with gp130, showing a similar kinetic behavior (Figure 10). The physiological role of these interactions could be explained considering that SAgs block gp130, preventing IL-6 stimuli and the activation of STAT-3 pathway, which is needed for the expression of IL-30 in monocytes (73). Since it has been suggested that IL-30 could be involved in the sepsis-control-modulating cytokines secreted by NKT cells (83), inhibition of the synthesis of IL-30 would suit the spread of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway does not use IL-6R: the IL-6 inhibitor, but the not IL-6R inhibitor, may interfere with EBI3-dependent signaling. In addition, IL-30, the p28 subunit of the heterodimeric cytokine IL-27, binds IL-6R and modulates inflammatory responses [130,131]. The IL-6R inhibitor, but not the IL-6 inhibitor, may interfere with IL-30 signaling.…”
Section: Recent Advancements In Il-6 Inhibitorsmentioning
confidence: 99%
“…In both mice and humans, IL-30/IL-6R activates signal transduction, solely via the β-receptor chain gp130, with subsequent STAT1 and STAT3 phosphorylation, without the need of WSX-1. In addition, IL-30 can also form a biologically active complex with sIL-6R, both in mice and in humans [69,77], which implies that IL-30 trans-signaling is possible on cells lacking membrane-bound IL-6R [69], a mechanism that enlarges the spectrum of IL-30 responsive cells to virtually all cells of the body, in analogy to IL-6. Such as for the best known and longer studied homologue cytokine IL-6 [78,79], a prominent role is emerging for IL-30 in tumorigenesis, given its ability in shaping the TME and cancer stem cell niche, in which myeloid cells are critically involved.…”
Section: Il-30 Immunobiology In Man and Mousementioning
confidence: 99%